EMPOWERMENT OF THE ELDERLY WITH HYPERTENSION THROUGH PROGRESSIVE MUSCLE RELAXATION EXERCISE AT UPT PSTW JEMBER - Arizal Al Farisi; Dinda Angelina Hariyono; Siti Nur Wahidah; Tantut Susanto (UNUSA Press, 2022)
Hypertension in the elderly is a common problem that is often found. Many factors affect hypertension in the elderly, so it is necessary to empower them elderly. The purpose of this empowerment to control the blood pressure of the elderly through progressive muscle relaxation (PMR) techniques. The method used is counselling and exercise demonstration, which consists of 3 main activities: screening, PMR technique training, and activity evaluation. The empowerment was attended by nine elderly at UPT PSTW Wisma Cempaka Jember. The evaluation of activities is to measure blood pressure with a stethoscope and sphygmomanometer. Wilcoxon statistical test was used to determine changes in blood pressure before and after PMR intervention. The elderly are 100% male, 55.6% are 60-70 years old, 44.4% live in an orphanage for 1-5 years, and 66.7% are from outside Jember and have itching 44.4%. The p-value was 0.02<0.05 in systole, which means there was a difference before and after PMR, and the p-value was 0.705>0.05 in diastole, which means there was no difference in blood pressure after PMR. PMR focuses on maintaining a relaxed state that can secrete CRH (Corticotropin-releasing Hormone) and ACTH (Adrenocorticotropic releasing hormone) so that adrenaline and non-adrenaline secretion decrease, which has an impact on heart contraction activity and decreased blood pressure. Elderly empowerment with progressive muscle relaxation can control blood pressure, specifically systolic, after one week of exercise. This exercise must be included in the PSTW exercise program, which can be done regularly to control blood pressure.